Chemistry and Biochemistry of Winemaking, Wine Stabilization and Aging 2021
DOI: 10.5772/intechopen.92445
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis-Related Proteins in Wine and White Wine Protein Stabilization

Abstract: Protein stabilisation in white wine is of great concern to winemakers as denaturation of wine proteins may cause haze formation, which is usually considered a wine fault. Pathogenesis-related (PR) proteins derived from grapes are the major soluble proteins remaining in the finished wine, which are mainly responsible for haze formation. The development of PR proteins in grapes during ripening and the extraction of PR proteins from grapes into juice can largely affect the concentration of PR proteins in the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…The table includes the operating conditions, range of protein reduction (%), and time of application for each technology. AF 2-3 g/L 67-95% [24][25][26] Physical-enzymaticmixed treatments High power ultrasound AF 30%/10 min; 60-90%/5-10 min n/a [27] Heat + enzymes BF 75 • C for 1 min + 15 mg/L of enzymes 1 81-84% [5] AF 75 • C for 2 min + 2 mL/L of enzymes 2 80-90% for CHI [28] Ultrafiltration AF 80% permeate/20% retentate, 10 kDa membrane n/a [29] Ultrafiltration + heat + enzymes AF 62 • C for 10 min + 30 mg/L of enzymes 1 30-96% [29] Immobilized enzyme supported on chitosan AF Continuous PBR 3 : 0.3-15 mL/min flow and 106-260 g/L 4-68% 61-63% [30,31] Adsorption-based treatments Magnetic nanoparticles coated with acrylic acid AF 10 W by 10 min (plasma deposition) and 13.3-25 g/L for 10 min >90% [32][33][34] Zeolites AF 4-8 g/L of zeolites for 1-3 h >90% [35,36] Roasted grape seeds powder BF 5-15 g/L for 1 h 37-85% [37,38] AF 25-32 g/L for 1 h 90-98% [37] Zirconium DF 25 g/L pellet in metallic cage for 3 days ~90% [39] AF Batch: 25 g/L for 72-192 h >70% [22] Continuous: 175-300 BV 4 (~5.7-3.3 g/L) for 30 min of residence time ~42% [40] Closed-loop operation: pellet packed (6.5 L), 300 L/h flow rate for 8-139 h ~54-60% [41,42] 1 Enzyme type: Proctase, prepared containing aspergillopesin I and II. 2 Enzyme type: Two proteases in aspergillopepsin-containing liquid preparations obtained from Aspergillus niger.…”
Section: White Wine Protein Stabilization Methods Without Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The table includes the operating conditions, range of protein reduction (%), and time of application for each technology. AF 2-3 g/L 67-95% [24][25][26] Physical-enzymaticmixed treatments High power ultrasound AF 30%/10 min; 60-90%/5-10 min n/a [27] Heat + enzymes BF 75 • C for 1 min + 15 mg/L of enzymes 1 81-84% [5] AF 75 • C for 2 min + 2 mL/L of enzymes 2 80-90% for CHI [28] Ultrafiltration AF 80% permeate/20% retentate, 10 kDa membrane n/a [29] Ultrafiltration + heat + enzymes AF 62 • C for 10 min + 30 mg/L of enzymes 1 30-96% [29] Immobilized enzyme supported on chitosan AF Continuous PBR 3 : 0.3-15 mL/min flow and 106-260 g/L 4-68% 61-63% [30,31] Adsorption-based treatments Magnetic nanoparticles coated with acrylic acid AF 10 W by 10 min (plasma deposition) and 13.3-25 g/L for 10 min >90% [32][33][34] Zeolites AF 4-8 g/L of zeolites for 1-3 h >90% [35,36] Roasted grape seeds powder BF 5-15 g/L for 1 h 37-85% [37,38] AF 25-32 g/L for 1 h 90-98% [37] Zirconium DF 25 g/L pellet in metallic cage for 3 days ~90% [39] AF Batch: 25 g/L for 72-192 h >70% [22] Continuous: 175-300 BV 4 (~5.7-3.3 g/L) for 30 min of residence time ~42% [40] Closed-loop operation: pellet packed (6.5 L), 300 L/h flow rate for 8-139 h ~54-60% [41,42] 1 Enzyme type: Proctase, prepared containing aspergillopesin I and II. 2 Enzyme type: Two proteases in aspergillopepsin-containing liquid preparations obtained from Aspergillus niger.…”
Section: White Wine Protein Stabilization Methods Without Additivesmentioning
confidence: 99%
“…The haze formation is mainly attributed to the slow denaturation of unstable proteins, which can occur during the storage or transport of white wines. The predominant haze-causing proteins are thaumatin-like proteins (TLPs) and chitinases (CHIs), which are grapes' derived pathogenesis-related (PR) proteins [2,4]. Other PR-proteins, such as β-glucanase, grape ripening-related proteins (GRIPs) like GRIP22 and GRIP32, invertase, and lipid transfer proteins (LTPs), have been identified as minor contributors to haze formation [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is rare in wines with relatively high levels of flavonoid phenols, particularly tannins, which complex and precipitates proteins during wine production. The most important proteins that have been related to wine protein instability are pathogenesis-related proteins of Vitis vinifera that include the chitinases and thaumatin-like proteins as described by Tian et al [23]. The formation of wine protein haze is a multifactorial process with several factors known to influence the process, such as storage or wine ageing temperature, pH, ionic strength, wine protein composition, organic acids, ethanol, phenolic compounds, metals, and sulphate content; however, other important factors remain unidentified, such as the non-proteinaceous component(s) usually named X factor [24].…”
Section: Protein Instabilitymentioning
confidence: 99%
“…Although the exact mechanism of protein haze formation is not very clear, it may be assumed that it is mainly associated with hydrophobic protein–phenolic interactions [ 2 ]. Furthermore, it has been observed that pathogenesis-related (PR) proteins (e.g., thaumatin-like proteins TLP and chitinase CH) derived from grapes are mainly responsible for haze formation in bottled white wine [ 3 ]. Van Sluyter et al [ 4 ] have proposed a revised mechanism of protein haze formation involving three different stages.…”
Section: Introductionmentioning
confidence: 99%
“…The most used method to treat white wine instability is the batch addition of bentonite at the end of wine ageing before bottling. This required treatment, in addition to being an additional time- and resource-consuming step, is associated with negative environmental impact (disposal of spent materials), product loss (3–10%) and quality degradation of wine at the end of its maturation [ 1 , 3 ], estimated to be about USD 1 billion per year [ 5 ]. To overcome these criticisms, several approaches have been studied to solve the question of protein instability in white wine, all of them suggesting their application on finished wine.…”
Section: Introductionmentioning
confidence: 99%